2018
DOI: 10.12659/msm.910279
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Operative Frozen Section Histology of the Pancreatic Resection Margins and Clinical Outcome of Patients with Adenocarcinoma of the Head of the Pancreas Undergoing Pancreaticoduodenectomy

Abstract: BackgroundThe aim of this study was to compare the clinical outcome in patients with pancreatic ductal adenocarcinoma who underwent frozen section and paraffin section histology of the surgical resection margins during pancreaticoduodenectomy.Material/MethodsFrozen section and routine paraffin section histopathology were performed using the following categories: R0 (no tumor cells at the surgical resection margin), R1 (tumor cells at, or within 1 mm, of the surgical resection margin), and R2 (tumor seen macros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Previous reports have shown a close relationship between R1 resection and OS (or DFS) in PDAC patients [10,[17][18][19]. Even for patients who underwent PD for PDAC with positive resection margins shown on frozen section, further surgical resection to achieve R0 did not have any signi cant positive impact on OS [20]. These studies suggested that it is vital to achieve R0 resection on the rst attempt of surgical resection.…”
Section: Discussionmentioning
confidence: 76%
“…Previous reports have shown a close relationship between R1 resection and OS (or DFS) in PDAC patients [10,[17][18][19]. Even for patients who underwent PD for PDAC with positive resection margins shown on frozen section, further surgical resection to achieve R0 did not have any signi cant positive impact on OS [20]. These studies suggested that it is vital to achieve R0 resection on the rst attempt of surgical resection.…”
Section: Discussionmentioning
confidence: 76%
“…Previous reports have shown a close relationship between R1 resection and OS (or DFS) in PDAC patients [10,[17][18][19]. Even for patients who underwent PD for PDAC with positive resection margins shown on frozen section, further surgical resection to achieve R0 did not have any signi cant positive impact on OS [20]. These studies suggested that it is vital to achieve R0 resection on the rst attempt of surgical resection.…”
Section: Discussionmentioning
confidence: 83%
“…It is possible to perform a cryobioptic examination of the resection lines and if they are tumorpositive, change the strategy of the operation and perform a more extensive procedure. In these cases the contribution to survival improvement is questionable, as the study of Mathur et al [15] and as well Dikman et al [16] has shown. Patients with R1 resection determined peroperatively by cryobiopsy clearly have a worse prognosis than patients with R0 resection.…”
Section: Discussionmentioning
confidence: 99%